Increased MHC matching by C4 gene compatibility in URD HSCT - Jonna Clancy; Jarmo Ritari; Muriel Lobier; Riitta Niittyvuopio; Urpu Salmenniemi; Mervi Putkonen; Maija Itälä-Remes; Jukka Partanen; Satu Koskela (Elsevier, 2022)
HLA matching is a prerequisite for successful allogeneic hematopoietic stem cell transplantation (HSCT) because it lowers the occurrence and severity of graft-versus-host disease (GVHD). However, matching a few alleles of the classic HLA genes only may not ensure matching of the entire MHC region. HLA haplotype matching has been reported to be beneficial in HSCT because of the variation relevant to GVHD risk in the non-HLA region. Because polymorphism in the MHC is highly population specific, we hypothesized that donors from the Finnish registry are more likely to be matched at a higher level for the Finnish patients than donors from other registries. In the present study we determined 25 single nucleotide polymorphisms (SNPs) of the complement component 4 (C4) gene in the γ-block segment of MHC from 115 Finnish HSCT patients and their Finnish (n = 201) and non-Finnish (n = 280) donor candidates. Full matching of HLA alleles and C4 SNPs, independently or additively, occurred more likely in the Finnish–Finnish group as compared with the Finnish–non-Finnish group (P < .003). This was most striking in cases with HLA haplotypes typical of the Finnish population. Patients with ancestral HLA haplotypes (AH) were more likely to find a full HLA and C4 matched donor, regardless of donor origin, as compared with patients without AH (P < .0001). Despite the clear differences at the population level, we could not find a statistical association between C4 matching and clinical outcome. The results suggest that screening C4 SNPs can be advantageous when an extended MHC matching or HLA haplotype matching in HSCT is required. This study also supports the need for small population-specific stem cell registries.